Hydroiodic Acid Additive Enhanced the Performance and Stability of PbS-QDs Solar Cells via Suppressing Hydroxyl Ligand - Yang, Xiaokun; Yang, Ji; Khan, Jahangeer; Deng, Hui; Yuan, Shengjie; Zhang, Jian; Xia, Yong; Deng, Feng; Zhou, Xue; Umar, Farooq; Jin, Zhixin; Song, Haisheng; et al. (Nano-Micro Letters, 2020)
The recent emerging progress of quantum dot ink (QD-ink) has overcome the complexity of multiple-step colloidal QD (CQD) film preparation and pronouncedly promoted the device performance. However, the detrimental hydroxyl (OH) ligands induced from synthesis procedure have not been completely removed. Here, a halide ligand additive strategy was devised to optimize QD-ink process. It simultaneously reduced sub-bandgap states and converted them into iodide-passivated surface, which increase carrier mobility of the QDs films and achieve thicker absorber with improved performances. The corresponding power conversion efficiency of this optimized device reached 10.78%. (The control device was 9.56%.) Therefore, this stratege can support as a candidate strategy to solve the QD original limitation caused by hydroxyl ligands, which is also compatible with other CQD-based optoelectronic devices. Highlights: 1 The hydroiodic acid was explored systematically to modify PbS quantum dots (QDs) ink process, which could remove trap states by hydroxyl ligand and improve iodine passivation on the PbS-QDs surface. 2 This strategy solved the essential question of PbS-QDs ink process and showed the favorable application prospects in QDs technology.